2019
DOI: 10.1039/c8nr06694a
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal dynamics in HfOx/AlOy-based homeothermic synaptic memristors with low-power and homogeneous resistive switching

Abstract: Homeothermic synaptic behaviors with a wide range of temperature were demonstrated in CMOS-compatible HfOx/AlOy memristors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…As shown in numerous previous studies, RRAM has been extensively reported to mimic synaptic characteristics [ 29 , 30 , 31 , 32 , 33 ] as well as to implement nonvolatile high-density memory [ 34 ]. Anion migration and metal ion migration are representative RRAM operation systems [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in numerous previous studies, RRAM has been extensively reported to mimic synaptic characteristics [ 29 , 30 , 31 , 32 , 33 ] as well as to implement nonvolatile high-density memory [ 34 ]. Anion migration and metal ion migration are representative RRAM operation systems [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike a passive nonlinear-resistive two-port emulator circuit, the bi-stability and multi-stability phenomena of Chua Corsage Memristors can be realized by a single device as demonstrated in recent literature [29][30][31]. The NbO 2 Mott memristor [29,30] exhibits an analogous dynamic route to that of 2-lobe CCM which has two stable and one unstable equilibrium points on its dynamic route map (dT/dt vs. T (Figure 1 [29])).…”
Section: Physical Realization Of Ccm Familymentioning
confidence: 99%
“…The universal formulas of switching kinetics (in Section 3) can be applicable to NbO 2 Mott memristor as the PWL dynamic route, and switching kinetics are explicitly similar to 2-lobe CCM. In addition, HfOx/AlOy-based homeothermic memristor [31] has a similar number of stable equilibrium states (i.e., four temperature-dependent equilibrium states corresponding to its four dynamic conductances (Figure 3 in [31])) to that of 6-lobe CCM. When driven by DC input, the homeothermic memristor exhibits four distinct DC V-I curves corresponding to its four temperature-dependent dynamic conductances (Figure 3e and f in [31]) which is identical to 6-lobe CCM (shown in Figures 2c and 10).…”
Section: Physical Realization Of Ccm Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic devices such as RRAM [15][16][17][18][19] and phase change memory (PRAM) [20,21] can reduce the burden of computation compared to a graphics processing unit (GPU)-based deep learning framework by employing weight updating by matrix multiplication. Moreover, a two-terminal RRAM device can 2 of 8 maximize memory density compared to three-terminal devices.…”
Section: Introductionmentioning
confidence: 99%